Determinants of banks performance in Brazil - Chew, Wye Foong; Chow, Pui Yee; Kang, Xiu-Yun; Khor, Chun Wei; Yew, Wan Yin (2019)
This purpose of this research is to identify the significance of the macroeconomics and bank-specific variables that will be affect the bank performance. Asset growth, liquidity, and leverage are the bank-specific factors, while gross domestic product (GDP), and inflation are the macroeconomic factors which selected to conduct this research. The five banks we chosen to do this research are Banco Bradesco S.A., Banco do Brasil S.A., Banco do Estado do Rio Grande do Sul S/A, Itau Unibanco, and Citigroup Inc. The data was collected on yearly basis from 1997 to 2017. The total sample size is 21. In this research, the variables that influence the banks’ performance will be tested by using EVIEWS.